case with abnormal tone decay and recruitment as measured by ABLB (auto) test - Vyasamurthy MN (Journal of All India Institute of Speech and Hearing, 1970)
A case of abnormal tone decay demonstrating recruitment is reported. If we accept that recruitment is an artifact, the findings of this case are typical of ABLB {auto presentation) test. On the other hand, if vie consider that recruitment is a fact the findings of this case are atypical of ABLB test indicating co-existence of the two lesions viz. cochlear and retrocochlear. If we accept that recruitment is an artifact, ABLB {auto) test is not a useful test in differential diagnosis of cochlear Vs. retrocochlear as recruitment measured by ABLB {auto) test is expected in all SN loss cases irrespective of tone decay provided factors like crossover, diplacusis, pulse rate and error of judgement are controlled.